Rituximab in the Treatment of Interstitial Lung Diseases Related to Anti-Melanoma Differentiation-Associated Gene 5 Dermatomyositis: A Systematic Review - He, Chenjia; Li, Wenyu; Xie, Qibing; Yin, Geng (Frontiers in Immunology, 2022)
Objective The effectiveness of rituximab in anti-melanoma differentiation-associated gene 5 (MDA5) dermatomyositis (DM) with interstitial lung disease (ILD) has been explored only in isolated case reports and small series. This paper aims to review the current evidence regarding rituximab (RTX) use in the treatment of ILD related to anti-MDA5 DM (anti-MDA5 DM-ILD). Methods We conducted a review by searching PubMed, Web of Science, Embase, and Cochrane for articles with information on patients with anti-MDA5 DM and RTX treatment, published until August 2021, in English language. The selected studies listed variation in chest high-resolution computed tomography (HRCT) and/or pulmonary function test (PFT) as a primary outcome, in patients with anti-MDA5 DM-related ILD after using RTX. Results Of the 145 potentially eligible articles, 17 were selected. The information gathered from a total of 35 patients with anti-MDA5 DM-ILD was reviewed, including 13 men and 22 women. Patient age at onset was 47.60 ± 13.72 years old. A total of 11.43% (4/35) of the patients were found to have chronic ILD (C-ILD) and 88.57% (31/30) exhibited rapidly progressive ILD (RP-ILD). Most patients (29/30) had typical DM rashes. Prior to RTX administration, the majority of patients (27/35) were treated with medium- or high-dose glucocorticoids and at least one additional immunotherapeutic agent. With regard to RTX efficacy for ILD in anti-MDA5 DM, 71.43% (25/35) of the patients responded to treatment. Skin rash also improved in more than half of the patients after RTX treatment. The most common side effects were infections, reported by 37.14% (13/35) of the patients after using RTX. Conclusion As a CD20 targeting drug, RTX is a promising therapeutic tool for anti-MDA5 DM-ILD, although the risk of infections should be considered before treatment. Further prospective controlled studies are required to evaluate the optimal RTX treatment regimen. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021289714, identifier CRD42021289714.